’Like Father, Like Son’? The Woman as Bargaining Object in Gen 20:1-18 and Gen 26:1-11 - Uzukwu, Gesila N. (Old Testament Essays, 2021)
Abraham and Isaac separately ‘used’ their wives to stay alive. Viewed, on one hand, as a pragmatic approach to life, the choice made by father and son demonstrates a moral failure that caused them to ‘sacrifice’ their wives, turning them to objects that could be exchanged. Hence, the end of preserving their lives justifies the means (lying and cooperation in formal evil of adultery). On the other hand, the story of Isaac, following in the footsteps of his father, offers us a reflection on how certain human actions, while useful and valid at a given point in time, cannot be judged morally good/bad or worthy of emulation without reference to the intention and historical situation of the primary agent. In Gen 20:1-18 and 26:1-11, the five protagonists (Abraham, Sarah, Isaac, Rebecca and Abimelech) confront us with the perennial issues of patriarchy, the agency and compliance of women in reinforcing patriarchal patterns of politics and de-humanisation, the resilience and resistance of women in the face of the many forms of objectification and commodification as well as the error of repeating the mistakes of the fathers. Using a biblical social ethical approach, this article examines (a) how patriarchalism could and have fostered the objectification and commodification of women; (b) what themes from father and son communicate to the modern reader about the interplay of cause and effect in fostering a culture of gender violence and instrumentalisation of women, as well as (c) how the female protagonists’ response to the situation of exploitation (especially sexual exploitation) and objectification could inspire modern women to break boundaries that negate female flourishing. https://doi.org/10.17159/2312–3621/2021/v34n1a7